Release of biologically active peptides from grape juice by Oenococcus oeni isolated from argentine wine - Stivala, Maria Gilda (2018)
The increase in biologically active peptides after proteolytic activity of Oenococcus oeni X2L was studied in grape juice medium (GJM) and in GJM fermented with Saccharomyces cerevisiae mc2. Sequential inoculation of O. oeni X2L with proteolytic activity in GJM before (“I” medium) and after (“F” medium) yeast fermentation allowed peptide release. In the “I” medium, bacterial proteolytic activity (0.083 mM) released 3.88 mg nitrogen (N) of peptides per liter and produced an increase of 203.39 µmol/L in the ferric reducing antioxidant power (FRAP) and 16.49% in the angiotensin I-converting enzyme inhibitory (ACE-I) activity after 48 hrs of incubation. In the “F” medium, a higher proteolytic activity was evidenced after 48 hrs of incubation (0.179 mM), releasing 0.87 mg N of peptides/L. The released peptides in the “F” medium produced an increase in ACE-I activity (22.15%). Calculation of the specific activity (activity expressed per mg N of peptide released) of FRAP, 1, 1-diphenyl-2-picrylhydrazyl scavenging, and ACE-I after 48 hrs of incubation revealed a higher activity in the “F” than in the “I” medium. This finding indicates a higher efficiency of the proteolytic system of O. oeni X2L on grape juice proteins in the release of bioactive peptides after yeast growth.